Biocicle: improving architecture and visualizations for the summarizing tool (2018)
The current project intends to extend the platform of BioCicle considering the current feedback and a constant support from potential users. In order to do this it was necessary to both strengthen the architecture to support the desired formats of sequence inputs and show summaries and detail tables that will not only be provide the users with a bigger insight but also will allow them to use the output inside their own researchs.